Emerging drugs for prostate cancer. (December 2013) - Chung, Paul H; Gayed, Bishoy A; Thoreson, Gregory R; Raj, Ganesh V
<x xml:space="preserve">Abstract</x> Introduction: Androgen deprivation therapy is the mainstay treatment for patients with prostate cancer who are not candidates for definitive treatment, are diagnosed with advanced disease on initial presentation or progress after primary treatment. Patients who stop responding to androgen deprivation therapy develop castration resistant prostate cancer (CRPC). Emerging drugs undergoing clinical evaluation and drugs that have recently received FDA approval for the treatment of CRPC are reviewed. Areas covered: As the natural history and signaling pathways of prostate cancer are better understood, new treatments and targeted therapies will be developed. The FDA recently approved 5 medications that increase survival in patients with CRPC. Additional medications and drug classes are being explored that may eventually lead to new treatment options. Articles were identified using a PubMed database search. Expert opinion: Recent FDA medication approvals and the development of emerging treatments are promising for the future of patients with prostate cancer. The addition of new medications challenges physicians to identify the optimal sequence and/or combination in which newer and older medications should be administered. Physicians treating patients with prostate cancer have a growing responsibility to keep pace with these new medications so that they may counsel and treat patients appropriately.